Efficacy of PBL Approach in Bahraini Context: Views and Reflections - Aljalahma, A. Alzayed (Journal of Education and Practice, 2023)
Purpose: After the implementation of Alzayed's research (2016), another research on the efficacy of PBL in the High school in Bahraini context was conducted using the same participants of Alzayed's research (2016). That was for two main reasons: First is to find out the process behind how students on the PBL scheme learn. The second is to detect if it has any positive or negative effect on them. Methodology: This paper adopted a qualitative approach and semi-structured interviews of twenty-four students, two teachers, and three curriculum specialists. Findings: Its main findings reflect that students who were taught Islamic Education (IE) under the umbrella of the PBL scheme, their critical thinking skills were significantly reinforced as much as the delivered knowledge which was smoothly adopted without any need to be forced or pressurized through the learning process. Simply, they were able to learn the information effortlessly. This research concludes that the PBL scheme was successful as students developed confidence in learning which enabled them to have positive attitudes towards learning. Although students had to adjust themselves to the different teaching and learning methods, they were able to work together positively and fruitfully. This research explored that students have good ambitions after using the PBL scheme. Unique Contribution to Theory, Policy and Practice: The study recommends that the Ministry of Education consider this by introducing the scheme as an effective and positive process to be used for students to learn and achieve better outcomes. Moreover, this research adds value to the PBL in the context of Islamic education in Bahrain as well as ensuring its effectiveness in learning and developing skills.